Macronutrient content and distribution in rambutan on the atlantic coast of Honduras - Sosa-Rodrigues, Breno Augusto (2020)
Introduction. Rambutan productivity depends on satisfying its nutritional demand through the use of fertilizers. Knowing the quantity and the times of greatest demand for nutrients by the plant allows the producer to improve fertilization programs. Objective. To evaluate the content and distribution of macronutrients in different ages of the rambutan crop. Materials and methods. An experiment was established in the Atlantic coast of Honduras under a completely randomized design with six treatments (sampling at 2, 3, 4, 8, 10, and 17 years of establishment) and three repetitions. The study was carried out between the months of March and December 2017. At harvest time, leaves, branches, shells, and seeds were collected to analyze the concentrations of N, P, K, Ca, Mg, and S in each one. Results. It was recorded that the macronutrient concentration differed significantly among the organs and ages of the plant, finding the highest concentration of N, Ca, Mg, and S in leaves, P in seed and K in the shell. The total concentration (leaf + branch + shell + seed) of the nutrients registered fluctuations over time and increased the demand for P, K, Ca, and Mg in years 2 and 3, to then decline in years 8 and 10. While the demand for N and S were constant during the development stages. In addition, N (41 %) was required in greater quantities, followed by K (24 %) and Ca (20 %) and finally P (6 %), Mg (5 %) and S (4 %). Conclusion. The content and distribution of macronutrients were variable according to the age of the plant, allowing the identification of which nutrients and when they were most required and the plant organ where it was accumulated.